2016
DOI: 10.1002/oby.21557
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between carbohydrate consumption and plasma adropin concentrations in humans

Abstract: Objective The role of metabolic condition and diet in regulating circulating levels of adropin, a peptide hormone linked to cardiometabolic control, is not well understood. Here we examined weight loss and diet effects on plasma adropin concentrations. Methods The present report includes data from (1) a weight loss trial, (2) an evaluation of acute exercise effects on mixed-meal tolerance test responses, and (3) a meta-analysis to determine normal fasting adropin concentrations. Results Plasma adropin conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 40 publications
(77 reference statements)
3
49
3
Order By: Relevance
“…Moreover, in line with the results of the current study and against that of Dąbrowski et al (47) multiple clinical trials approved the negative relation between ADR serum level and blood glucose and IR whereas Stevens et al (49) reported that ADR levels in humans are sensitive to dietary macronutrients, perhaps due to habitual consumption of carbohydrate-rich diets suppressing circulating ADR levels. Zhang et al (50) found IR index is a negative independent risk factor of ADR levels in obese adolescents.…”
Section: Discussion:-supporting
confidence: 89%
“…Moreover, in line with the results of the current study and against that of Dąbrowski et al (47) multiple clinical trials approved the negative relation between ADR serum level and blood glucose and IR whereas Stevens et al (49) reported that ADR levels in humans are sensitive to dietary macronutrients, perhaps due to habitual consumption of carbohydrate-rich diets suppressing circulating ADR levels. Zhang et al (50) found IR index is a negative independent risk factor of ADR levels in obese adolescents.…”
Section: Discussion:-supporting
confidence: 89%
“…It was shown that in women but not in men, serum adropin concentration positively correlated with fat intake [20]. In addition, humans with low adropin levels consume more carbohydrates (simple and complex carbohydrates) [21]. Nevertheless, it is unknown whether diet affects adropin levels or whether adropin influences nutritional habits.…”
Section: Modulation Of Adropin By Body Mass Index (Bmi) Diet and DImentioning
confidence: 99%
“…The relationships between adropin and metabolism in humans are less clear and remain under investigation. Several studies have reported that fasting plasma adropin concentrations are lower in humans with insulin resistance (23)(24)(25)(26). Relationships have been observed between circulating adropin concentrations and fasting glucose levels in children with Prader-Willi syndrome, as well as circulating levels of the gut peptide obestatin in children (27).…”
Section: Mouse Studies Linking Adropin a Peptide Hormone Encoded Bymentioning
confidence: 99%
“…A more recent study using diverse age groups observed an inverse association between plasma adropin concentrations and indices of atherogenic hypercholesterolemia (total cholesterol, LDL-C, and nonHDL-C) in males possibly mediated by suppression of ENHO expression by cholesterol (8). In adults, plasma adropin concentrations are positively correlated with dietary fat intake and inversely with carbohydrate intake (26,28) and increase during fructose consumption (29). Differences in dietary preferences (fat versus carbohydrates) could be a confounding variable in cross-sectional human studies examining the relationship between circulating adropin levels and indices of cardio-metabolic risk.…”
Section: Mouse Studies Linking Adropin a Peptide Hormone Encoded Bymentioning
confidence: 99%